Disparities in healthcare access experienced by Hispanic chronic kidney disease patients: a cross-sectional analysis - Sadia Anjum Ashrafi; Rifat Binte Alam; Alicia Kraay; Babatope Ayokunle Ogunjesa; Andiara Schwingel (BMC, 2024)
Abstract Background Chronic kidney disease (CKD) is a public health concern, and the disease disproportionately affects Hispanics. Improved healthcare access for Hispanic CKD patients can reduce the disease burden. This study assesses the healthcare access disparities experienced by Hispanic CKD patients compared to Whites. Methods We analyzed three National Health and Nutrition Examination Survey (NHANES) datasets for 2013-2014, 2015-2016, and 2017-2018. The primary predictor variable was race, and the outcome variable was three domains of healthcare access: insurance status, having any routine place for healthcare, and having any health visits in the past year. Chi-square tests and unadjusted and adjusted multivariate logistic regressions were conducted. The models were adjusted for age, education, income, and CKD stages and were weighted to account for the sampling strategy. Results The sample size was 1864 CKD patients from three two-year cycles of NHANES datasets (2013-2014, 2015-2016, and 2017-2018). The final adjusted model found that Hispanic CKD patients were more likely to be uninsured (OR: 2.52, CI 1.66-3.83) and have no routine place for healthcare (OR: 1.68, CI 1.03-2.75) than White CKD patients, but did not have differences in healthcare visits in the past year. Conclusions Hispanic CKD patients have limited healthcare access compared to White populations showing existing care access disparities experienced by them. Improved programs and policies are required to enhance kidney health among Hispanics and promote equity in CKD.